Pewartaan Injil Melalui Jual-Beli Kopi dan Noken: Upaya Inkulturasi terhadap Umat Asli Papua di Paroki Modio - Biru Kira (JURNAL PASTORAL KATEKETIK, 2024)
The focus of this research is to answer the question of how the Gospel is preached to the people of Indigenous Papuans (OAP) in Santa Maria Bunda Rosario Parish, Modio. This research uses a qualitative method by conducting a process of participatory observation and involvement as an 'insider', and the data is analyzed phenomenologically or using a hermeneutic approach. The results obtained from this research are that the preaching of the gospel is carried out through efforts to develop the people's economy based on the reality of the community's attachment to their land and forest products, by buying and selling coffee and noken. The community enthusiastically participates in this economic development program because this effort has answered their longing for salvation now and here in accordance with the challenges of daily life.